Life-cycle exposure to environmental copper pyrithione causes multigenerational developmental and reproductive toxicity in medaka - Sutapa Debi; Can Tang; Mingfeng Li; Hongdong Fang; Jiezhang Mo; Wenhua Liu (Marine Pollution Bulletin, 2026)

Mechanical behavior of pipe umbrellas at tunnel portal sections under elastically restrained end conditions - Haiwei Shang; Chaojun Jia; Mingfeng Lei; Chenghua Shi; Jianyuan Tang (Tunnelling and Underground Space Technology, 2026)

Digital twin modelling of shield tunneling undercrossing existing tunnels: A case study - Qiujing Pan; Yiming Zhang; Cong Tang; Weibo Luo; Zihan Yang; Mingfeng Lei (Tunnelling and Underground Space Technology, 2026)

Conjunctive analysis of BSA-Seq and KASP markers unveils the preliminary candidate genes controlling chalkiness of rice grain - Mingfeng Tang; Zhongwei Wang; Tingting Zeng; Tingting Fu; Wei Zhang; Yongchuan Huang; Yanjie Yao; Yongyang Fan; Xianwei Zhang (Euphytica, 2026)

Molten Li/Na/K ternary carbonate salt pyrolysis of biomass: A facile approach for co-production of porous biochar, CO-enriched syngas, and high-selectivity bio-oil - Jiazhen Tang; Tianyu Lu; Xing Xie; Dan Lin; Dongjing Liu; Qingfa Zhang; Mingfeng Wang; Weiwei Liu; Zhong Ma; Haiping Yang; Shihong Zhang; Bin Li (Journal of Cleaner Production, 2026)

Underlying mechanism of sucrose esters on myofibrillar protein O/W emulsion gel behaviour under different ionic strengths: Focus on emulsion characterisation, protein structural changes and molecular interactions - Xiang Li; Bo Wang; Wenwen Hou; Jie Tang; Hongbin Lin; Junqiang Lian; Qian Liu; Mingfeng Xu; Yuan Ma; Dong Yu; Dong Zhang; Jiaxin Chen (Food Chemistry, 2025)

Combined techniques for antigen-specific nanobody discovery in the white-spotted bamboo shark (Chiloscyllium plagiosum) - Bo Zhong; Junjie Yang; Kaixi Zheng; Wenjie Tang; Lei Jia; Mingfeng Gu; Jinming Hu; Xiaofeng Jiang; Jianqing Chen; Zhengbing Lyu; Guodong Chen (Fish & Shellfish Immunology, 2025)

Isolation and structural elucidation of two novel lignans from the flowers of Gardenia jasminoides with potent α-glucosidase inhibitory activity - Qingsen Shao; Huiyu Li; Mingfeng Li; Wei Yi; Qiugui Zhou; Lijuan Zheng; Meng Wang; Hong-mei Hu; Chao Wen; Yun Tang; Wei Li (Phytochemistry Letters, 2025)

Optimizing chemical topping in cotton: Effects of planting density and variety sensitivity to mepiquat chloride - Yanqin Wu; Chaoyuan Tang; Mingwei Du; Jingshan Tian; Mingfeng Yang; Yali Zhang; Wangfeng Zhang (Field Crops Research, 2025)

Multi-classification prediction of PM2.5 concentration based on improved adaptive boosting rotation forest - Tan Deng; Yingzi Jia; Ni Liu; Xiaoyong Tang; Mingfeng Huang; Wenzheng Liu; Xinjiang Hu; Yanling Gu (Journal of Environmental Chemical Engineering, 2024)

Current Status and Future Trends in Installation, Operation and Maintenance of Offshore Floating Wind Turbines - Mingfeng Hu; Jinkun Shi; Sheng Yang; Mingsheng Chen; Yichang Tang; Suqian Liu (Journal of Marine Science and Engineering, 2024)
The installation and operation phases are critical stages in the lifecycle of offshore wind turbines, with costs associated with the installation and maintenance of floating wind turbines accounting for approximately 50% of the total investment. This paper presents the latest advancements in the technologies for the installation and maintenance of floating wind turbines. First, it discusses the installation techniques and relevant research related to the foundations and components of floating wind turbines. Next, it explores various operational strategies for offshore wind turbines and studies on major component replacements. The interrelationship of research in the installation and maintenance fields for floating wind turbines is examined. Furthermore, this paper investigates various tools and equipment used for the installation and maintenance of offshore wind turbines. It also addresses the relevant regulations and standards governing offshore operations for floating wind turbines. Finally, this paper provides a forward-looking perspective on the installation and maintenance of floating wind turbines.

Performance Comparison of Sea Cucumber Detection by the Yolov5 and DETR Approach - Xin Yuan; Shutong Fang; Ning Li; Qiansheng Ma; Ziheng Wang; Mingfeng Gao; Pingpeng Tang; Changli Yu; Yihan Wang; José-Fernán Martínez Ortega (Journal of Marine Science and Engineering, 2023)
Sea cucumber detection represents an important step in underwater environmental perception, which is an indispensable part of the intelligent subsea fishing system. However, water turbidity decreases the clarity of underwater images, presenting a challenge to vision-based underwater target detection. Therefore, accurate, real-time, and lightweight detection models are required. First of all, the development of subsea target detection is summarized in this present work. Object detection methods based on deep learning including YOLOv5 and DETR, which are, respectively, examples of one-stage and anchor-free object detection approaches, have been increasingly applied in underwater detection scenarios. Based on the state-of-the-art underwater sea cucumber detection methods and aiming to provide a reference for practical subsea identification, adjacent and overlapping sea cucumber detection based on YOLOv5 and DETR are investigated and compared in detail. For each approach, the detection experiment is carried out on the derived dataset, which consists of a wide variety of sea cucumber sample images. Experiments demonstrate that YOLOv5 surpasses DETR in low computing consumption and high precision, particularly in the detection of small and dense features. Nevertheless, DETR exhibits rapid development and holds promising prospects in underwater object detection applications, owing to its relatively simple architecture and ingenious attention mechanism.

Seasonal pollution and surface characteristics of microplastics in surface water in the Wanzhou section of the Three Gorges Reservoir, China - Ying He; Qian Huang; Qilong Wang; Mingfeng Tang; Xiaoyu Lu; Fei Cheng; Guosheng Xiao (Environmental Science and Pollution Research, 2023)
The pollution of freshwater environments with microplastics (MPs) has attracted increasing attention owing to their threats to aquatic ecosystems and human health. Here, we sampled and analyzed MPs from mainstream, tributary, and backwater areas in the Wanzhou section of the Three Gorges Reservoir (TGR) in impoundment and flood periods. Microplastic pollution was the most severe in the backwater areas. The average abundance of MPs reached the highest value in the flood period (5.27±3.47×10 7 items km −2 ), which was 3–5 times that in the impoundment period. In the 0.3–5 mm size class, the 1–5 mm fraction was the most abundant, accounting for more than 81% in the flood period and 68% of the total MP particle abundance in the impoundment period in the mainstream and backwater areas. However, 0.3–1 mm MPs contributed more than 50% in the tributaries during the impoundment period. Polystyrene, polypropylene, and polyethylene MPs were detected in foam, fragment, sheet, and line-shaped MP particles. White, opaque, foamed polystyrene MPs contributed 32–81% to total MP particle abundance in the watershed. Microplastic particle surfaces showed signs of damage and oxidation, and ten different elements were found. Oxygen was clustered on the surface of foam and fragment MPs. Microplastic pollution was severe in the Wanzhou watershed. Especially in the backwater areas, oxidized MPs of variable shapes derived mainly from surface runoff in the flood period and sewage discharge in the impoundment period were abundant. The results of this study contribute to understanding seasonal pollution patterns and surface characteristics of MPs in the TGR and similar watersheds.

Effects of Microplastics on the Mineral Elements Absorption and Accumulation in Hydroponic Rice Seedlings (Oryza sativa L.) - Mingfeng Tang; Yongchuang Huang; Wei Zhang; Tingting Fu; Tingting Zeng; Yongdong Huang; Xiaoxia Yang (Bulletin of Environmental Contamination and Toxicology, 2022)

Antisense oligonucleotide technology can be used to investigate a circular but not linear RNA-mediated function for its encoded gene locus - Zhenxing Song; Ruirui Jia; Mingfeng Tang; Fei Xia; Haiyang Xu; Zhengguo Li; Chuan Huang (Science China Life Sciences, 2021)

Calculation Model of Supporting System for Tunnel Under Shallow and Weak Surrounding Rock Considering the Synergistic Effects - Haorong Cao; Limin Peng; Mingfeng Lei; Qianlong Tang; Long Peng; Fudong Chen (Geotechnical and Geological Engineering, 2020)

Causes Analysis, Reinforcement and Repair Technology of Segment Crack and Damage During Shield Tunnelling Process: A Case Study - Cao Haorong; Peng Limin; Lei Mingfeng; Chen Fudong; Tang Qianlong (Geotechnical and Geological Engineering, 2019)

Scaffold-based design of xanthine as highly potent inhibitors of DPP-IV for improving glucose homeostasis in DIO mice - Yan Ran; Heying Pei; Caifeng Xie; Liang Ma; Yuzhe Wu; Kai Lei; Mingfeng Shao; Minghai Tang; Mingli Xiang; Aihua Peng; Yuquan Wei; Lijuan Chen (Molecular Diversity, 2015)